Biomarker profiles of endothelial activation and dysfunction in rare systemic autoimmune diseases: implications for cardiovascular risk. (18th August 2020) - Wienke, Judith; Mertens, Jorre S; Garcia, Samuel; Lim, Johan; Wijngaarde, Camiel A; Yeo, Joo Guan; Meyer, Alain; van den Hoogen, Lucas L; Tekstra, Janneke; Hoogendijk, Jessica E; Otten, Henny G; Fritsch-Stork, Ruth D E; et al.
Abstract: Objectives: Vasculopathy is an important hallmark of systemic chronic inflammatory connective tissue diseases (CICTD) and is associated with increased cardiovascular risk. We investigated disease-specific biomarker profiles associated with endothelial dysfunction, angiogenic homeostasis and (tissue) inflammation, and their relation to disease activity in rare CICTD. Methods: A total of 38 serum proteins associated with endothelial (dys)function and inflammation were measured by multiplex-immunoassay in treatment-naive patients with localized scleroderma (LoS, 30), eosinophilic fasciitis (EF, 8) or (juvenile) dermatomyositis (34), 119 (follow-up) samples during treatment, and 65 controls. Data were analysed by unsupervised clustering, Spearman correlations, non-parametric t test and ANOVA. Results: The systemic CICTD, EF and dermatomyositis, had distinct biomarker profiles, with 'signature' markers galectin-9 (dermatomyositis) and CCL4, CCL18, CXCL9, fetuin, fibronectin, galectin-1 and TSP-1 (EF). In LoS, CCL18, CXCL9 and CXCL10 were subtly increased. Furthermore, dermatomyositis and EF shared upregulation of markers related to interferon (CCL2, CXCL10), endothelial activation (VCAM-1), inhibition of angiogenesis (angiopoietin-2, sVEGFR-1) and inflammation/leucocyte chemo-attraction (CCL19, CXCL13, IL-18, YKL-40), as well as disturbance of the Angiopoietin-Tie receptor system and VEGF-VEGFR system. These profiles were related to disease activity, and largely normalized during treatment. However, a subgroup of CICTD patients showed continued elevation of CXCL10, CXCL13, galectin-9, IL-18, TNFR2, VCAM-1, and/or YKL-40 during clinically inactive disease, possibly indicating subclinical interferon-driven inflammation and/or endothelial dysfunction. Conclusion: CICTD-specific biomarker profiles revealed an anti-angiogenic, interferon-driven environment during active disease, with incomplete normalization under treatment. This warrants further investigation into monitoring of vascular biomarkers during clinical follow-up, or targeted interventions to minimize cardiovascular risk in the long term.